Nectary development in Cleome violacea - Carey, Shane; Zenchyzen, Brandi; Deneka, A. J.; Hall, Jocelyn C. (Frontiers in Plant Science, 2023)
Nectaries are a promising frontier for plant evo-devo research, and are particularly fascinating given their diversity in form, position, and secretion methods across angiosperms. Emerging model systems permit investigations of the molecular basis for nectary development and nectar secretion across a range of taxa, which addresses fundamental questions of whether there is convergence or divergence in the genetic basis of nectary formation and nectar secretion. Herein, we explore nectary development and nectar secretion in the emerging model taxa, Cleome violacea (Cleomaceae), which exhibits a prominent adaxial nectary. First, we characterized nectary anatomy and quantified nectar secretion to establish a foundation for quantitative and functional gene experiments. Next, we leveraged RNA-seq to establish gene expression profiles of nectaries across three key stages of development: pre-anthesis, anthesis, and post-fertilization. We then performed functional studies on five genes that were putatively involved in nectary and nectar formation: CvCRABSCLAW (CvCRC), CvAGAMOUS (CvAG), CvSHATTERPROOF (CvSHP), CvSWEET9, and a highly expressed but uncharacterized transcript. These experiments revealed a high degree of functional convergence to homologues from other core Eudicots, especially Arabidopsis. CvCRC, redundantly with CvAG and CvSHP, are required for nectary initiation. Concordantly, CvSWEET9 is essential for nectar formation and secretion, which indicates that the process is eccrine based in C. violacea. While demonstration of conservation is informative to our understanding of nectary evolution, questions remain. For example, it is unknown which genes are downstream of the developmental initiators CvCRC, CvAG, and CvSHP, or what role the TCP gene family plays in nectary initiation in this family. Further to this, we have initiated a characterization of associations between nectaries, yeast, and bacteria, but more research is required beyond establishing their presence. Cleome violacea is an excellent model for continued research into nectary development because of its conspicuous nectaries, short generation time, and close taxonomic distance to Arabidopsis.